Characterization of BiOCl nanoplates synthesized by PVP-assisted hydrothermal method and their photocatalytic activities - Anukorn Phuruangrat (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. Visible-light-driven BiOCl nanoplates were successfully synthesized by polyvinylpyrrolidone (PVP)-assisted hydrothermal method. Effect of PVP weight content on structure, atomic vibration and morphology of the products was investigated. Pure phase of uniform tetragonal BiOCl nanoplates with ± (001) top and bottom and ± (110) side and end exposed surfaces was successfully synthesized in the solutions containing 0.00–1.00 g PVP by hydrothermal method at 180 °C for 24 h. The as-prepared BiOCl nanoplates with different weight contents of PVP adding were studied for photodegradation of rhodamine B (RhB) under visible light irradiation of a xenon lamp. In this research, BiOCl nanoplates with PVP adding exhibit photocatalytic activity higher than BiOCI nanoplates without PVP adding.